Islamic Finance at Crossroads - Al-Jarhi, Mabid (Intellectual Discourse, 2018)
After more than 40 years of practice, the Islamic finance industry is composed of products with claim of Islamicity but questionable on their Shariʽah credentials. The industry is increasingly exposed to cynicism and decline in popular interest. This paper restates the essence of riba prohibition from an economic perspective. It evaluates the Shariʽah scholars approach to validation of contracts as well as the monetary authorities’ attitude towards the Shariʽah content of Islamic finance transactions. It points out the advantages of Islamic finance within an Islamic macroeconomic environment. It looks into the problem of convergence of Islamic finance to conventional finance, and reasons behind the convergence. This study finds that several violations of the true paradigm of Islamic finance are because of its advantages being all external and impossible to internalize. The paper concludes with some proposals for checking the convergence.